Can the ATM and TP53 levels influence the low metastasis potential of canine TVT? - Huppes, R. R.; Carvalho, M.; Ferreira, T. M. M. R. [UNESP]; Granja-Salcedo, Y. T. [UNESP]; Uscategui, R. A. R. [UNESP]; Castro, J. L. C.; Josiani, P. M. [UNESP]; De Nardi, A. B. [UNESP]; Amorim, R. L. [UNESP] (Univ Austral Chile, Fac Ciencias Veterinarias, 2016)
The study of metastatic progression mechanisms of TVT is necessary. Several prognostic markers have been studied, including ATM genic and protein expression. When present in low expression, this gene is associated to neoplastic progression and low survival rates, especially in mammary neoplasms in humans. The main function of TP53 is to interrupt cell cycle and DNA repair or to induce the apoptosis. Therefore, it is suggested that the loss of its function may allow mutated cells to accumulate more mutations, and even inactivate others suppressor and proto oncogenes, favoring the development and onset of neoplasms. This study aimed to evaluate ATM and TP53 gene expression in TVT. Thirty two canine TVT samples that had their mRNA extracted and submitted to qRT-PCR technique were used. The results were compared to peripheral blood of 10 healthy dogs as control group. At the evaluation of the transcript ATM gene it was observed a significant increase expression in tumoral tissue (TVT) (P < 0.0001) when compared to control group. However, the TP53 gene showed similar transcript gene between tumor tissue (TVT) (P = 0.26) and control group. These factors may explain the low metastatic rate.
Keywords: expression; metastatic invasion; tumoral suppressor genes